The Role of Social Media Marketing and E-WOM in Influencing Purchase Intention - Pahlawan, Muhammad Reza Rizqi; Cahyono, Sugianto Eko; Yoestini (Economic and Business Horizon, 2025)
The increasing digitalization of consumer behavior in Indonesia has significantly reshaped marketing dynamics, urging Micro, Small, and Medium Enterprises (MSMEs), particularly in the Food and Beverage (F&B) sector, to adopt more cost-effective, targeted, and interactive online marketing strategies. Among the most influential digital tools are Social Media Marketing (SMM) and Electronic Word-of-Mouth (e-WOM), which play a vital role in shaping consumer purchase intentions by enhancing brand visibility, credibility, and engagement. Despite the growing relevance of these tools in the digital ecosystem, research exploring their integrated effects on consumer behavior remains limited, especially within the MSME context. This study seeks to examine the influence of SMM and e-WOM on consumer purchase intention by offering a comprehensive analysis of how digital marketing strategies impact behavioral outcomes. A quantitative method was applied, utilizing regression analysis through SPSS version 25 to assess data collected from respondents actively engaged with Indonesian MSMEs on platforms such as Instagram and TikTok. The findings reveal that social media marketing exerts a significant influence on purchase intention, both partially and simultaneously, when combined with e-WOM factors. These results are expected to enhance the theoretical framework surrounding digital marketing effectiveness and provide practical insights for MSMEs in Indonesia aiming to increase brand loyalty and drive purchase conversions through strategic and engaging online approaches.